Polymorphic Variants in NR1I3 and UGT2B7 Predict Taxane Neurotoxicity and Have Prognostic Relevance in Patients With Breast Cancer: A Case‐Control Study. Issue 2 (28th March 2019) - Arbitrio, Mariamena; Scionti, Francesca; Altomare, Emanuela; Di Martino, Maria Teresa; Agapito, Giuseppe; Galeano, Teresa; Staropoli, Nicoletta; Iuliano, Eleonora; Grillone, Francesco; Fabiani, Fernanda; Caracciolo, Daniele; Cannataro, Mario; et al.
Abstract : Taxane‐related peripheral neuropathy (TrPN) is a dose‐limiting toxicity with important interindividual variability. Genetic polymorphisms in absorption, distribution, metabolism, and excretion (ADME) genes may account for variability in drug efficacy and/or toxicity. By the use of Affymetrix drug‐metabolizing enzyme and transporter microarray platform, in a retrospective case‐control study, the correlation between ADME polymorphic variants and grades ≥ 2−3‐TrPN was investigated. In a breast cancer (BC) training set, five single‐nucleotide polymorphisms in NR1I3 and UDP‐glucuronosyltransferase ( UGT ) 2B7 genes were correlated to grades ≥ 2−3‐TrPN protection. By receiver operating characteristic curves, the grades ≥ 2−3‐TrPN‐related candidate biomarkers in an independent series of 54 patients with BC (17 cases and 37 controls) were validated. NR1I3 was correlated to paclitaxel‐TrPN and UGT2B7 to docetaxel‐TrPN. Moreover, a genetic signature of prognostic relevance for BC outcome was found. Our findings might have potential relevance for personalized management of patients with BC for prevention of treatment failure in ultrametabolizer genetic variants.